Monozygotic twins discordant for Aicardi syndrome. Issue 8 (August 1997) - Costa, T; Greer, W; Rysiecki, G; Buncic, J R; Ray, P N
Abstract : Aicardi syndrome is a developmental disorder characterised by agenesis of the corpus callosum, retinal lacunae, seizures, and developmental delay. It is believed to be X linked with lethality in males. We report a set of monozygotic female twins one of whom is healthy and intellectually normal while the other has the classical Aicardi phenotype with profound retardation. Family history is negative. Both had normal karyotypes. Monozygosity was established by blood grouping, chromosomal heteromorphisms, and DNA analysis using six hypervariable probes (five autosomal and one X linked) and three X linked RFLP probes. We tested the hypothesis that preferential inactivation of a different X chromosome had occurred in each girl. Methylation sensitive RFLP analysis of DNA from EBV transformed B lymphocytes and cultured skin fibroblasts using MspI/HpaII digestion and probing with M27 beta showed a very similar pattern of X inactivation in both twins with no evidence of preferential expression of one particular X chromosome. We conclude that the abnormalities in the affected twin are probably the consequence of a postzygotic mutation in early embryonic development.